AB0994 Impact on the adherence and persistence of denosumab vs weekly bisphosphonate in health-related quality of life in postmenopausal osteoporosis. (12th June 2018) - Carlino, G.; Cinzia, R.; Maggio, R.
Abstract : Background: Long term adherence and persistence in patients undergoing treatment for postmenopausal osteoporosis remains poor despite the proven efficacy of the therapy. Objectives: In this study, we evaluated whether greater adherence and persistence in treatment can lead to an improvement in the quality of life. Methods: A cohort of 268 patients, all women, in postmenopausal osteoporosis divided into two groups was evaluated: "DEN Group" (DEN) in treatment with denosumab (n=131) and "BIS Group" (BIS) in treatment with bisphosphonates (n=137). Table 1 shows demographic and clinical data. Patients were followed for 3 years with baseline, 6 month, 18 month, and 36 month evaluation. The evaluation criteria were the persistence in therapy and the self-related treatment compliance, as well as the quality of life assessed with the 41-item Quality of Life questionnaire for osteoporosis (QUALEFFO-41) performed at baseline, at 18 and at 36 months. Results: Table 2 shows the percentage of patients who abandoned treatment at different times with a statistical significance towards both 18 and 36 months. In the BIS the main reason for abandonment were the adverse events (gastrointestinal, dental interventions, etc.), in the DEN the abandonment was due to drop-out. [In BIS, the most frequent reason for non-compliance with therapy was oversight, and most patients who continued treatment always used the drugs regularly on the recommended days and dosages.] In the period of time considered the majority of patients both BIS and DEN said they were satisfied with the treatment and wanted to continue it. The QUALEFFO scores (Fig 1) of patients from the baseline visit were significantly improved in the 36 month visit (BIS 79.6±25.4 vs 65.4±14.6; DEN 80.2±18.5 vs 55.6*±16.4 (*p<0.001); the difference was not significant between BIS and DEN groups at both baseline visit and 36 month visit, but in the DEN group there was significance between baseline and 36 month visit. OC=Osteocalcin, CTX=C terminal telopeptide, PTH=parathyroid hormone, 25OHD=25 hydroxyvitamin D; Abstract AB0994 – Table 2 Percentage of patients who abandoned. Conclusions: In conclusion, the observation, although numerically limited, notes that the use of denosumab in patients with postmenopausal osteoporosis leads to a greater persistence in treatment and a statistically significant adherence to therapy, which allows to obtain the maximum therapeutic effect of the therapy, also determining in 36 months of treatment an improvement in the quality of life, which is not achieved in subjects treated with bisphosphonates. Disclosure of Interest: None declared